SECULAR VARIATION IN THE COMPOSITION OF BASALTS: AN INDEX TO MANTLE EVOLUTION - Condie Kent C. (My University, 1985)
At the same Mg-number, a decrease is observed in the average content of Ni, Co, and Cr in basalts between 2.5 and 2.0 b.y. Such decreases can be accounted for by smaller degrees of melting in the mantle in response to falling geotherms. In terms of partially compatible (e.g. Ti, Zr, Nb, Y) and incompatible elements (e.g. Rb, Sr, Ba), Archean basalts are similar to modern island-arc basalts although they are relatively enriched in Th and Zr and depleted in Al. The upper concentration limit of partially compatible and incompatible elements increases in basalts between 2?5 and 1.0 b.y. Basalts with large concentrations of these elements do not appear to have been produced during the Archean and become important in the geologic record only after 1?0 b.y. ago. Varying degrees of melting, fractional crystallization, or crustal contamination are not capable of accounting for these changes, and an increasing importance of enriched mantle sources seems necessary. A greater availability of enriched mantle sources after the Archean may reflect recycling of ancient enriched mantle or continental sediments into the mantle during catastrophic continental growth at 2.7 b.y.
Keywords: Archean; Precambrian::Archean; Докембрий::Архей